The Role of Work Climate in Mediating the Relationship of Spiritual Leadership and Creative Behavior - Muhammad Ikhsan Fifaldyovan (SEAN Institute, 2024)
Employee creative behavior is a requirement for innovative behavior, which is a form of HR excellence that supports the success and sustainability of the organization. The research aims to analyze the role of work climate in mediating the relationship between spiritual leadership and employee creative behavior. The research used a quantitative approach with subjects of 140 private employees in Semarang who were obtained by incidental sampling. Data was obtained using a questionnaire and analyzed using path analysis and Sobel test. Research results: Workplace climate mediates the relationship between spiritual leadership and creative behavior. Organizational leaders must demonstrate spiritual qualities and activities to deal with subordinates' actions in complex and challenging situations so subordinates can behave creatively.